ChemInform Abstract: Convenient Copper‐Mediated Chan—Lam Coupling of 2‐Aminopyridine: Facile Synthesis of N‐Arylpyridin‐2‐amines. Issue 47 (November 2015) - Chen, Jianbin; Natte, Kishore; Man, Nikki Y. T.; Stewart, Scott G.; Wu, Xiao‐Feng
Abstract: The title reaction shows good functional group tolerance but sterically demanding boronic acids such as (IIc) give only low yields.